It's complicated : the social lives of networked teens - boyd, danah, 1977- (New Haven : Yale University Press, 2014)
An absolutely essential read, written by a leading expert, for anyone who wants to understand young people's use of social media.
Identity: why do teens seem strange online? -- Privacy: why do youth share so publicly? -- Addiction: what makes teens obsessed with social media? -- Danger: are sexual predators lurking everywhere? -- Bullying: is social media amplifying meanness and cruelty? -- Inequality: can social media resolve social divisions? -- Literacy: are today's youth digital natives? -- Searching for a public of their own.
Includes bibliographical references and index.
Keywords: Internet and teenagers; Online social networks; Teenagers -- Social life and customs -- 21st century; Information technology -- Social aspects